Modelling Tools for Active Classification in Shallow Water Environments. - Huelsnitz, Warren G. (1994)
Several tools have been developed, primarily using MATLAB, for modeling the active return of a target in an arbitrary, three-dimensional ocean environment and for quantifying the environmental distortion and interference. An acoustic model based on ray theory is used to compute the target echo and reverberation. These tools have been applied to Barents Sea and Gulf of Sidra ocean environments for a billboard transmit/receive any of 23 equally spaced elements. The frequency dependence of a sonar target's echo depends on its size, shape, wall thickness, and acoustic impedance. Active classification involves using this signature', or transfer function, to classify the target and reduce or eliminate false alarms. Complications arise due to the signal distortion that occurs in inhomogeneous ocean environments, particularly in shallow water. Multiple paths, reverberation, and ambient noise modify the received signal and make it difficult to extract the target's response. It is hoped that these tools will provide insight into the modelling and signal processing requirements for active classification as well as realistic signals for testing various schemes.